2013
DOI: 10.1007/s00300-013-1384-7
|View full text |Cite
|
Sign up to set email alerts
|

Hydrographic influences on the summer dive behaviour of Weddell seals (Leptonychotes weddellii) in Atka Bay, Antarctica

Abstract: In order to gain insights into species-level behavioural responses to the physical environment, it is necessary to obtain information from various populations and at all times of year. We analysed the influences of physical environmental parameters on the mid-summer dive behaviour of Weddell seals (Leptonychotes weddellii) from a little-known population at Atka Bay, Antarctica. Dive depth distributions followed a typical bimodal pattern also exhibited by seals from other populations and seals targeted both sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…This may indicate differences in the vertical depth distribution of prey species associated with differences in the temperature gradient of the water column*possibly suggesting aggregations of suitable prey at deeper depths in more stratified water masses, and more scattered distributions of prey in weakly stratified water masses (Takahashi et al 2008). Similar relationships between dive parameters of Weddell seals and the temperature stratification of the water column were described recently by McIntyre et al (2013).…”
Section: Water Temperature Influences On Dive Behavioursupporting
confidence: 70%
See 1 more Smart Citation
“…This may indicate differences in the vertical depth distribution of prey species associated with differences in the temperature gradient of the water column*possibly suggesting aggregations of suitable prey at deeper depths in more stratified water masses, and more scattered distributions of prey in weakly stratified water masses (Takahashi et al 2008). Similar relationships between dive parameters of Weddell seals and the temperature stratification of the water column were described recently by McIntyre et al (2013).…”
Section: Water Temperature Influences On Dive Behavioursupporting
confidence: 70%
“…Residuals from the regression were then used to identify dives of increased ''forage effort'', based on above-average amounts of time spent at the bottoms of dives for particular dive depths and durations. Bottom time residuals as an indicator of foraging effort was previously used by a number of authors studying both elephant and Weddell (Leptonychotes weddellii) seals (Bailleul et al 2008;McIntyre, Ansorge et al 2011;Heerah et al 2013;McIntyre et al 2013). While Dragon et al (2012) reported inconclusive relationships between bottom time residuals and evident increased foraging (negative bottom time residuals for deeper ''active'' dives and positive bottom time residuals for shallower ''active'' dives) in southern elephant seals, the results reported by Gallon et al (2013) and Robinson et al (2010) lend further support to this method.…”
Section: Divesmentioning
confidence: 99%
“…A study by McIntyre et al . () tagged four adult Weddell seals with an equal sex ratio and found no sex effect for the maximum distance traveled from the location that they had been tagged. All adult seals tagged within Queen Maud Land remained with 15 km of the tagging location.…”
Section: Discussionmentioning
confidence: 99%
“…The mean bathymetry recorded for diving Weddell seals in Queen Maud Land was 207 m (McIntyre et al . ), in Dumont d'Urville was 237 m (Heerah et al . ), and in the Western Ross Sea was 505 m (Goetz ).…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies use changes in surface GPS track patterns [1518] or diving behaviour [1922] as foraging indices. In various predator species, resource acquisition has been linked to a type of behaviour called area-restricted search (ARS) [23].…”
Section: Introductionmentioning
confidence: 99%